A Comparative Study on Development of MSMEs and Policies in Indonesia and Malaysia - Nurulhasanah Abdul Rahman; Zulnaidi Yaacob; Ida Busneti; Tulus Tambunan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
Based on secondary data and existing literature, this paper discusses current development of micro, small and medium enterprises (MSMEs) and their main constraints in two key member states of ASEAN, Malaysia and Indonesia. The selection of these two countries is based on two main considerations. First, Malaysia and Indonesia (together with Singapore and Thailand) have been the key engines of economic growth in ASEAN. Second, given their huge number, MSMEs in these two states are expected to play a key role in the development of ASEAN MSMEs as well as in contributing to economic growth of the region. The paper also discusses MSMEs development policies in these two countries.